Religious Conversion in Africa - Bruner, Jason; Hurlbut, David Dmitri (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This collection brings together a diverse range of scholars, including historians of pre-colonial, colonial, and contemporary Africa, along with anthropologists, who develop fresh arguments and reassessments of religious, cultural, and social change pertaining to Africa. The result is a fascinating array of research that offers critical, creative, and constructive analyses of religious change on the African continent, from the medieval period to the present.